Minireview: Long Noncoding RNAs: New “Links” Between Gene Expression and Cellular Outcomes in Endocrinology - Sun, Miao (Endocrine Society, 2013)
Recent advances in sequencing technologies have revealed that the genome is extensively transcribed, yielding a large repertoire of noncoding RNAs. These include long noncoding RNAs (lncRNAs), mRNA-like molecules that do not code for proteins, which are emerging as a new class of RNAs that play important roles in a variety of cellular processes. Ongoing studies are revealing new insights about lncRNAs, including their physiological functions, disease relationships, and molecular mechanisms of action. Characterized lncRNAs have been shown to interact with and modulate the activity of other RNAs and protein partners, leading to alterations in transcriptional and posttranscriptional regulatory processes. In this review, we summarize the key features of lncRNAs, their molecular mechanisms of action, biological functions, and therapeutic implications, particularly as they apply to the field of molecular endocrinology. In addition, we provide a brief overview of how molecular biologists are beginning to probe the identity, mechanisms, and functions of this emerging class of RNA molecules.